Status of Land Tenure and Contribution of Its Utilization to Farmers' Household Incomes in Outskirts Dompu District Forest Area - Fatun Anggraini; Halil Halil; Muhammad Siddik (IKIP Mataram, 2022)
This study aims to identify the status of land tenure and use by farming households in the outskirts of the forest area and analyze household income from sharing sources and the contribution of agricultural business income to household incomes in the forest area of Dompu Regency. This study uses a descriptive method with the unit of analysis of farmer households in the outskirts of the forest area of Dompu Regency. This sample area was determined by purposive sampling. Determination of the number of respondents is determined by probability sampling with the determination of respondents by Cluster Random Sampling. The results showed that most of the land tenure on the outskirts of the forest area was cultivator, around 85.33% with a land area of 1.79 ha and 1.33% with an area of 0.03 ha on dry land. And paddy fields with tenant owner status are around 45.33% with an area of 0.30 Ha. Meanwhile, in HKM with non-owner cultivator status or about 20.00% with an area of 0.20 Ha. The average area of land controlled by farmers is in the range of > 1.0 Ha as many as 61 respondents. The land use is corn, rice and livestock commodities. Land tenure causes several impacts, both in terms of land that will continue to experience damage and environmental damage such as floods and landslides. And the contribution of agricultural business income to the household income of farmers on the outskirts of the forest area is 61.42%, compared to the contribution of income from outside the agricultural business of 34.55% and other incomes of 4.04%. Thus, it is suggested to the government to increase the extension program on how to cultivate annual crops that can provide maximum production yields and to farmers to plant annual crops of high economic value according to market demand by taking into account the condition of agricultural land and geographical location.